Recognition of the Y chromosome in Turner syndrome using peripheral blood or oral mucosa tissue - Lene Garcia Barbosa; Adriana Aparecida Siviero-Miachon; Maria Anunciação Souza; Angela Maria Spinola-Castro (Korean Society of Pediatric Endocrinology, 2021)
Purpose Turner syndrome is defined as total or partial loss of the second sex chromosome in a phenotypically female patient. Due to the possibility of hidden mosaicism of fragments of the Y chromosome and development of gonadoblastoma, we evaluated the presence of such fragments in 2 tissues with different embryonic origins, peripheral blood lymphocytes (mesoderm), and oral mucosal cells (ectoderm) using multiplex polymerase chain reaction. Methods DNA samples were collected from 109 patients, and primers for the SRY, TSPY, and AMELX genes were used. Results We found 14 patients (12.8%) with positive molecular markers for the Y chromosome. The study of tissues of different embryological origin showed the same degree of agreement, sensitivity, and specificity. Conclusions Oral mucosa cells have a simpler method of collection that is less invasive and requires less time for DNA extraction at a lower cost.